Magnetic evolution and anomalous Wilson transition in diagonal phosphorene nanoribbons driven by strain. (2nd July 2015) - Zhang, Shuai; Li, Chong; Xiao Guo, Zheng; Cho, Jun-Hyung; Su, Wan-Sheng; Jia, Yu
Abstract: Inducing magnetism in phosphorene nanoribbons (PNRs) is critical for practical applications. However, edge reconstruction and Peierls distortion prevent PNRs from becoming highly magnetized. Using first-principles calculations, we find that relaxed oxygen-saturated diagonal-PNRs (O-d-PNRs) realize stable spin-polarized antiferromagnetic (AFM) coupling, and the magnetism is entirely localized at the saturated edges. The AFM state is quite stable under expansive and limited compressive strain. More importantly, not only does the irreversible Wilson transition occur when applying strain, but the nonmagnetic (NM) metal phase (a new ground state) becomes more stable than the AFM state when the compressive strain exceeds −4%. The related stability and transition mechanism are demonstrated by dual tuning of the geometric and electronic structures, which manifests as a geometric deviation from a honeycomb to an orthorhombic-like structure and formation of P- p y bonding (P- p z nonbonding) from P- p z nonbonding (P- p y antibonding) because of the increase of the proportion of the P- p y (P- p z ) orbital.